Pluripotent Stem Cell‐Based Platforms in Cardiac Disease Modeling and Drug Testing. Issue 2 (17th July 2017) - Shaheen, N; Shiti, A; Gepstein, L
Abstract : The ability to generate patient/disease‐specific human pluripotent stem cell (hPSC)‐derived cardiomyocytes (hPSC‐CMs) brings a unique value to the fields of cardiac disease modeling, drug testing, drug discovery, and precision medicine. Further integration of emerging innovative technologies such as developmental‐biology inspired differentiation into chamber‐specific cardiomyocyte subtypes, genome‐editing, tissue‐engineering, and novel functional phenotyping methodologies should facilitate even more advanced investigations. Here, we review cornerstone concepts and recent highlights of hPSC‐based cardiac disease modeling and drug testing.